Treatment of painful bone metastases in prostate and breast cancer patients with the therapeutic radiopharmaceutical rhenium-188-HEDP - Lange, Rogier; Overbeek, Floor; de Klerk, John M. H.; Pasker-de Jong, Pieternel C. M.; van den Berk, Alexandra M.; ter Heine, Rob; Rodenburg, Cees J.; Kooistra, Anko; Hendrikse, N. Harry; Bloemendal, Haiko J. (Nuklearmedizin - NuclearMedicine, 2016)
Aim: Rhenium-188-HEDP (188Re-HEDP) is an effective radiopharmaceutical for the palliative treatment of osteoblastic bone metastases. However, only limited data on its routine use are available and its effect on quality of life (QoL) has not been studied. Therefore, we evaluated the clinical benefit of 188Re-HEDP in routine clinical care. Patients and methods: Prostate or breast cancer patients with painful bone metastases receiving 188Re-HEDP as a routine clinical procedure were eligible for evaluation. Clinical benefit was assessed in terms of efficacy and toxicity. Pain palliation and QoL were monitored using the visual analogue scale (VAS), corrected for opioid intake, and the EORTC QLQ-C30 Global health status/QoL-scale. Thrombocyte and leukocyte nadirs were used to assess haematological toxicity. Results: 45 and 47 patients were evaluable for pain palliation and QoL, respectively. After a single injection of 188Re-HEDP, the overall pain response rate was 69% and mean VAS-scores decreased relevantly and significantly (p < 0.05). Repeated treatment resulted in similar pain response. The overall QoL response rate was 68% and mean Global health status/QoL-scores increased relevantly and significantly. Haematological side effects were mild and transient. Conclusion: The clinically relevant response on pain and quality of life and the limited adverse events prove clinical benefit of treatment with 188Re-HEDP and support its use in routine clinical care. Its effectiveness appears comparable to that of external beam radiotherapy.
Keywords: Bone metastases; radionuclide therapy; rhenium- 188-HEDP; pain palliation; quality of life; haematological toxicity